(untitled) (Circe de clásicos y modernos, 2023)
Among the lessons drawn by Irenaeus from the third temptation of Jesus in the desert (Adv. Haer. 5. 22. 2), the deceitful nature of the senses and the need not to be surprised by riches, by worldly glory and by present phantasy (praesenti phantasia) stand out. The Greek term φαντασία, which has its Latin equivalent in imaginatio, had been widely analyzed in Stoic Logic, before undergoing certain changes over time that confined it to the field of Psychology. Linked to assent (συνκατάθεσις) and appetitus, it drags the wise man into error. The novelty of St. Irenaeus consists in giving fantasy a religious nuance, that of the illusory aspect of the sensible world which engenders deceptive images in those who contemplate it.